Intracapsular Enucleation of Intraparotid Facial Nerve Schwannoma with Intratemporal Extension - Linger SIM; Xing Yi YEOH; Tay Eng TAN; Zahirrudin ZAKARIA; Irfan MOHAMAD (Medeniyet Medical Journal)
Intraparotid facial nerve schwannoma is a rare condition, which is difficult to preoperatively diagnose without a definite biopsy, yet the diagnosis is important for surgical planning and avoiding accidental injury to the facial nerve. Considering the benign indolent nature of the schwannomas, the management should be prioritized on the long-term tumor control with special attention to the facial nerve function and facial cosmesis. Microscope-assisted intracapsular enucleation is an excellent treatment option for such lesions. Our patient showed House–Brackmann grade II facial function after the surgery. This technique is safe and offers a favorable outcome of facial nerve function.